Autoamputation of the Appendix in a Chronic Adnexal Abscess. (13th February 2018) - Markey, C. Michele; Vestal, Lauren E.
Abstract : Autoamputation of the appendix has rarely been described in the literature. We present a case of a pelvic mass, thought to be a dermoid cyst based on preoperative imaging. After surgical removal and pathological examination, the mass was found to be a chronic pelvic abscess containing the right adnexa as well as an autoamputated vermiform appendix. Differentiating between gynecologic and gastrointestinal disease preoperatively can be difficult and often a definitive diagnosis cannot be made until surgical exploration and pathological review. However, to our knowledge, this is the first described case of a chronic pelvic abscess containing an autoamputated vermiform appendix.